Epidemiological characteristics of employees malaria cases in the Zaporozhye region for the 2001 – 2019 years - Onishchenko, T. E.; Saveliev, V. G.; Ushenina, N. S.; Furyk, O. O.; Riabokon, Yu. Yu.; Оніщенко, Тетяна Євгенівна; Савельєв, Валерій Григорович; Ушеніна, Ніна Степанівна; Фурик, Олена Олександрівна; Рябоконь, Юрій Юрійович (Інститут епідеміології та інфекційних хвороб ім. Л.В. Громашевського НАМН України, 2019)
Malaria, because of the enormous damage to public health and economy of different countries, remains a global problem for humanity. Approximately 250 million cases are reported annually, with the vast majority accounting for African countries (92%), Southeast Asia (5%) and Eastern Mediterranean (3%). Up to 435,000 people die each year from malaria, 98% of which are tropical malaria cases. According to WHO, no significant progress has been made in reducing malaria in the world. Over the last 2 years, there has been a slowdown in malaria mortality rates due to declining international and local funding, as well as the ongoing process of building antimalarial drug resistance (https://www.who.int/malaria/media/world-malaria-report-2018/ru/). In the context of modern migration processes, the problem of imported malaria is of particular importance.